Association between primary Sjögren's syndrome and pregnancy complications: a systematic review and meta-analysis. Issue 8 (August 2016) - Upala, Sikarin; Yong, Wai; Sanguankeo, Anawin
Abstract Systemic autoimmune disorders may interfere with normal reproductive function resulting in negative outcome of pregnancy. Primary Sjögren's syndrome (pSS) is a common rheumatic disease that mostly affects females. There are many reports that this condition may increase risk of pregnancy complications and fetal loss. However, data regarding these adverse outcomes are scarce and inconclusive. We performed a systematic review and meta-analysis of available articles that assess the association between pSS and adverse pregnancy outcome. We comprehensively searched the databases of MEDLINE and EMBASE from their dates of inception to March 2016 and reviewed papers with validity criteria. A random-effects model was used to evaluate pregnancy complications in patients with pSS and healthy controls. From 20 full-text articles, 7 studies involving 544 patients and 1586 pregnancies were included in the meta-analysis. Fetal complications included spontaneous abortion, stillbirth, neonatal deaths, and intrauterine growth retardation. Compared with healthy pregnancy, patients with pSS had significantly higher chance of neonatal deaths (pooled odds ratio (OR) = 1.77, 95 % confidence interval (CI) 1.28 to 1.46, p  = 0.01). However, there were no significant associations between pSS and premature birth (OR = 2.10, 95 % CI 0.59–7.46, p  = 0.25), spontaneous abortion (OR = 1.46, 95 % CI 0.72–2.93, p  = 0.29), artificial abortion (OR = 1.12, 95 % CI 0.52–2.61, p  = 0.71), or stillbirth (OR = 1.05, 95 % CI 0.38–2.97, p  = 0.92). There is an increased risk of fetal loss in pregnant patients with pSS. The presented evidence further supports multidisciplinary care for these patients to prevent complications during pregnancy.